Commensal Microbiota Regulation of Metabolic Networks During Olfactory Dysfunction in Mice - Wang H (Dove Medical Press, 2020)
Haiyang Wang,1,2,* Lanxiang Liu,1,3,* Xuechen Rao,1,2,* Tingjia Chai,1,* Benhua Zeng,4 Xiaotong Zhang,1 Ying Yu,1 Chanjuan Zhou,1 Juncai Pu,1,3 Wei Zhou,1 Wenxia Li,4 Hanping Zhang,1,3 Hong Wei,4 Peng Xie1–3 1NHC Key Laboratory of Diagnosis and Treatment on Brain Functional Diseases, The First Affiliated Hospital of Chongqing Medical University, Chongqing 400016, People’s Republic of China; 2College of Biomedical Engineering, Chongqing Medical University, Chongqing 400016, People’s Republic of China; 3Department of Neurology, The First Affiliated Hospital of Chongqing Medical University, Chongqing 400016, People’s Republic of China; 4Department of Laboratory Animal Science, College of Basic Medical Sciences, Third Military Medical University, Chongqing 400038, People’s Republic of China*These authors contributed equally to this workCorrespondence: Peng XieNHC Key Laboratory of Diagnosis and Treatment on Brain Functional Diseases, The First Affiliated Hospital of Chongqing Medical University, 1 Youyi Road, Yuzhong District, Chongqing 400016, People’s Republic of ChinaTel +86-23-68485490Email xiepeng@cqmu.edu.cnHong WeiDepartment of Laboratory Animal Science, College of Basic Medical Sciences, Third Military Medical University, Chongqing 400038, People’s Republic of ChinaTel +86-23-68752051Email weihong63528@163.comIntroduction: Recently, an increasing number of studies have focused on commensal microbiota. These microorganisms have been suggested to impact human health and disease. However, only a small amount of data exists to support the assessment of the inﬂuences that commensal microbiota exert on olfactory function.Methods: We used a buried food pellet test (BFPT) to investigate and compare olfactory functions in adult, male, germ-free (GF) and specific-pathogen-free (SPF) mice, then examined and compared the metabolomic profiles for olfactory bulbs (OBs) isolated from GF and SPF mice to uncover the mechanisms associated with olfactory dysfunction.Results: We found that the absence of commensal microbiota was able to influence olfactory function and the metabolic signatures of OBs, with 38 metabolites presenting significant differences between the two groups. These metabolites were primarily associated with disturbances in glycolysis, the tricarboxylic acid (TCA) cycle, amino acid metabolism, and purine catabolism. Finally, the commensal microbiota regulation of metabolic networks during olfactory dysfunction was identified, based on an integrated analysis of metabolite, protein, and mRNA levels.Conclusion: This study demonstrated that the absence of commensal microbiota may impair olfactory function and disrupt metabolic networks. These findings provide a new entry-point for understanding olfactory-associated disorders and their potential underlying mechanisms.Keywords: gut microbiota, germ-free, olfactory bulb, metabolomic, gas chromatography-mass spectrometry